Effects of processing parameters on the reversible phase transition of germanium telluride - Haoran Ma; Shaorui Yang; Yi Liu; Yaguang Ye; Le Liu; Lei Liu; Wei Xiong; Leimin Deng; Tianting Chen (Journal of Materials Research and Technology)
The tunable and reversible manufacturing function of stealth metamaterials is of great practical significance to adapt to complex electromagnetic environment. However, the low fault tolerance of existing manufacturing methods limits their further development and utilization. In this article, the microstructure evolution and phase transition mechanism of germanium telluride (GeTe) film under different deposition conditions, laser modes, and scanning parameters were investigated. The experimental results show that sputtering pressure and laser pulse width have important effects on the deposition and modulation of GeTe. There are sputtering pressure threshold (SPT) and pulse width threshold (PWT), which determine the crystallization evolution mode and phase transition performance of GeTe film, respectively. For each sputtering pressure and laser pulse width, there are optimal sputtering power and repetition induction times to achieve the best film deposition quality and reverse phase transition function. Finally, the rewritable broadband lossy absorber (RBLA) is fabricated based on laser induction research, which can achieve low reflection stealth function in the range of 8.4–15.7 GHz. After repeated induction, the performance of RBLA remains the same, which is consistent with simulation results. The process and mechanism of GeTe in the fabrication and modulation stage are systematically analyzed and discussed for the first time, which provides a new solution and good candidate for the fabrication and modulation of stealth materials.